2002
DOI: 10.1002/aqc.505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of marine reserve protection on spiny lobster (Jasus edwardsii) abundance and size at Tonga Island Marine Reserve, New Zealand

Abstract: ABSTRACT1. Diving surveys were undertaken to investigate the effects of marine reserve protection on spiny lobster (Jasus edwardsii) populations at Tonga Island Marine Reserve, northern South Island, New Zealand over a 2 year period from December 1998 to December 2000.2. Spiny lobsters were 2.8 times more abundant overall, and mean size was 19 mm carapace length larger in shallow transects and 28 mm carapace length larger in deep transects, in the marine reserve than at adjacent fished sites. That pattern was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 29 publications
8
34
0
Order By: Relevance
“…Previous studies of S. serrata in Moreton Bay have found higher catches of crabs in summer compared to winter (Williams & Hill 1982). Our results are consistent with similar studies in which increases in catch rates (CPUE) of invertebrates have been detected in reserves worldwide (gastropod and sea urchin, Castilla 1996; gastropod, sea urchin and limpet, Castilla & Fernandez 1998; abalone and lobster, Edgar & Barrett 1999;lobster, Kelly et al 2000, Davidson et al 2002. Interestingly, the catch rates of S. serrata were almost identical between both marine reserves despite the Tripcony Bight reserve being 3 times larger in size than the Willes Island reserve.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies of S. serrata in Moreton Bay have found higher catches of crabs in summer compared to winter (Williams & Hill 1982). Our results are consistent with similar studies in which increases in catch rates (CPUE) of invertebrates have been detected in reserves worldwide (gastropod and sea urchin, Castilla 1996; gastropod, sea urchin and limpet, Castilla & Fernandez 1998; abalone and lobster, Edgar & Barrett 1999;lobster, Kelly et al 2000, Davidson et al 2002. Interestingly, the catch rates of S. serrata were almost identical between both marine reserves despite the Tripcony Bight reserve being 3 times larger in size than the Willes Island reserve.…”
Section: Discussionsupporting
confidence: 91%
“…The skewed size distribution of male crabs in both marine reserves in this study further reflects the impact the mud crab fishery has in Moreton Bay. Increases in the average size of crustaceans have also been detected in marine reserves for spiny lobster Jasus edwardsii in New Zealand (Kelly et al 2000, Davidson et al 2002 and American lobster Homarus americanus in Newfoundland (Rowe 2002). In contrast, the average size of female S. serrata in our study did not differ greatly between the reserve and non-reserve sites which is probably due to the total protection offered to female crabs at all study sites.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…These studies have generally shown higher values closer to reserve centres for target species of low to moderate mobility. Similar results have been obtained in the few lobster studies available (Kelly et al 2002, Davidson et al 2002. The most convincing evidence of benefits to nearby fisheries from this type of study is the build-up of reef fish biomass (for over 2 decades) adjacent to a marine reserve in the Philippines (Russ et al 2004).…”
Section: Introductionsupporting
confidence: 80%
“…Rock lobsters and large carnivorous fish have been shown to increase in size and abundance in temperate marine protected areas (MPAs) in Tasmania (Edgar & Barrett 1997, Barrett et al 2009) and New Zealand (Babcock et al 1999, Davidson et al 2002, Shears & Babcock 2002. Structural features such as crevices, holes or overhangs can offer physical refuges to reduce the predatory efficiency of these predators (Drolet et al 2004a), dampening their impact on prey populations.…”
Section: Introductionmentioning
confidence: 99%